Association of Early β-Amyloid Accumulation and Neuroinflammation Measured With [11C]PBR28 in Elderly Individuals Without Dementia - Toppala Sini; Ekblad Laura L.; Tuisku Jouni; Helin Semi; Johansson Jarkko J.; Laine Hanna; Löyttyniemi Eliisa; Marjamäki Päivi; Blennow Kaj; Zetterberg Henrik; Jula Antti; Viitanen Matti; et al. (United States, 2025)
OBJECTIVE: To examine whether early β-amyloid (Aβ) accumulation and metabolic risk factors are associated with neuroinflammation in elderly individuals without dementia. METHODS: We examined 54 volunteers (mean age 70.0 years, 56% women, 51% APOE ɛ4 carriers) with the translocator protein (TSPO) tracer [11C]PBR28 to assess neuroinflammation and with [11C] Pittsburgh compound B (PiB) to assess cerebral Aβ accumulation. [11C]PBR28 and [11C]PiB standardized uptake value ratios (SUVRs) were quantified in 6 regions of interests by using the cerebellar cortex as a pseudo-reference and reference region, respectively. Fasting venous glucose, insulin, and high-sensitivity C-reactive protein (hs-CRP) values were determined. Homeostatic model assessment of insulin resistance (HOMA-IR) was calculated. A subset of individuals (n = 11) underwent CSF sampling, and Aβ40, Aβ42, total tau, phospho-tau, soluble TREM2, and YKL-40 levels were measured. RESULTS: Among the whole study group, no significant association was found between [11C]PiB and [11C]PBR28 SUVR composite scores (slope 0.02, p = 0.30). However, higher [11C]PiB binding was associated with higher [11C]PBR28 binding among amyloid-negative ([11C]PiB composite score ≤1.5) (TSPO genotype-, age- and sex-adjusted slope 0.26, p = 0.008) but not among amyloid-positive (slope -0.004, p = 0.88) participants. Higher CSF soluble TREM2 (rs = 0.72, p = 0.01) and YKL-40 (rs = 0.63, p = 0.04) concentrations were associated with a higher [11C]PBR28 composite score. Higher body mass index, HOMA-IR, and hs-CRP were associated with higher [11C]PBR28 binding in brain regions where Aβ accumulation is first detected in Alzheimer disease. CONCLUSIONS: While there was no association between amyloid and neuroinflammation in the overall study group, neuroinflammation was associated with amyloid among the subgroup at early stages of amyloid pathology. Copyright © 2021 The Author(s). Published by Wolters Kluwer Health, Inc. on behalf of the American Academy of Neurology.